The Effects of Green Financing Drives on the Performance of DSE Listed Banks in Bangladesh - Alam, Md. Ashraful; Hossain, Dr. Syed Zabid (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
All commercial banks must take green financing drives to promote environmental-friendly projects in their mainstream investment. The purpose of the study is to feed an inclusive overview of the green finance (GF) situation emphasis on bank performance in Bangladesh. The secondary data were collected from Bangladesh bank annual reports, sustainability reports, other commercial banks' reports etc. from 2014 to 2023. SPSS software was applied to interpret the data. The results of the data analysed show GF have a significant impact on bank profitability. Regression model 1 indicates that energy efficiency and the recycling and manufacturing of recycling goods have the most positive impact on bank performance. Regression model 2 identifies that renewable energy impacts the most on bank performance. The possible future essence of this study is to convince bankers and policy planners that GF can be the best solution for surviving in the competitive market and improving bank profitability.